Soil Insect Diversity In The Cultivation Of Xanthosoma Undipes K. Koch In Talaga Warna Village, Serang Regency - Dharmawan, Aldi; Hermita, Nuniek; Saylendra, Andree; Rumbiak, Julio Eiffelt Rossafelt (Jurnal Agroekoteknologi Terapan, 2025)
Talas beneng (Xanthosoma undipes K.Koch) is an endemic plant species originating from Banten Province, specifically distributed in Serang Regency. Soil insects are those that inhabit and are active on or within the soil. Information regarding the diversity of soil insects in Talaga Warna Village, particularly within talas beneng cultivation areas, remains limited. This study aimed to determine the diversity and functional roles of soil insects associated with talas beneng cultivation in Talaga Warna Village, Pabuaran Subdistrict, Serang Regency. The research was conducted from November 2024 to January 2025. This study employed a quantitative descriptive method with an exploratory approach. Sampling was performed using purposive sampling with pitfall traps. Identified soil insects were analyzed using the Shannon-Wiener diversity index and dominance index. The identification results revealed a total of 326 soil insect individuals collected from the talas beneng cultivation habitat, belonging to seven families. The Shannon-Wiener diversity index value obtained was 1.332, indicating moderate diversity. The dominance index value was 0.368, suggesting low dominance within the community. Four ecological roles of soil insects were identified: predator, herbivore, pollinator, and detritivore. Keywords: Talas beneng (Xanthosoma undipes), soil insects, biodiversity, agricultural ecology, identification